2009
DOI: 10.4319/lo.2010.55.2.0560
|View full text |Cite
|
Sign up to set email alerts
|

Potential carbon fixation via methane oxidation in well‐oxygenated river bed gravels

Abstract: Due to a combination of local methanogenesis and high background concentrations in the groundwater, water in the River Lambourn is 51 times supersaturated with methane (162 nmol CH 4 L 21 ). Pore-water concentrations of methane in the gravels of the riverbed were much lower throughout the year (71 nmol CH 4 L 21 ), suggesting significant methane oxidation. To investigate the potential for methane oxidation as a novel chemosynthetic source of carbon to the food web, we made simultaneous measurements, in laborat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
44
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 30 publications
(47 citation statements)
references
References 36 publications
3
44
0
Order By: Relevance
“…Whilst the mesocosms did not have extensive hyporheic zones, conditions were consistent with that observed in many headwater streams, where the majority of macrofauna are confined to surface sediments and shallow oxygenated interstices (Trimmer et al, 2010), and substrata provided physical refugia for suitably adapted species during drying disturbances (Harris, 2006). Physicochemical conditions were highly congruent among the mesocosms (Table 1; Harris et al, 2007 To protect the rights of the author(s) and publisher we inform you that this PDF is an uncorrected proof for internal business use only by the author(s), editor(s), reviewer(s), Elsevier and typesetter SPi.…”
supporting
confidence: 76%
“…Whilst the mesocosms did not have extensive hyporheic zones, conditions were consistent with that observed in many headwater streams, where the majority of macrofauna are confined to surface sediments and shallow oxygenated interstices (Trimmer et al, 2010), and substrata provided physical refugia for suitably adapted species during drying disturbances (Harris, 2006). Physicochemical conditions were highly congruent among the mesocosms (Table 1; Harris et al, 2007 To protect the rights of the author(s) and publisher we inform you that this PDF is an uncorrected proof for internal business use only by the author(s), editor(s), reviewer(s), Elsevier and typesetter SPi.…”
supporting
confidence: 76%
“…The concentration of dissolved oxygen in the sediment was then measured at a resolution of 100 to 200 m (depending on the overall depth of penetration), using a 50-m oxygen sensor (OX50; Unisense AS, Denmark) attached to an automated micromanipulator controlled by microprofiling software (SensorTrace PRO; Unisense). The four longer sediment cores (50 cm long by 8.8 cm) were completely topped up with bottom water and then fitted with a cap equipped with a small rotating (400 rpm) magnetic flea and a cable gland for holding an oxygen electrode (25). The oxygen concentration in the water overlying the sediment was logged at 5-min intervals using oxygen electrodes (OX50; Unisense AS, Denmark) connected to in-line amplifiers and a four-channel data-logging meter (UnderWater meter; Unisense).…”
Section: Methodsmentioning
confidence: 99%
“…Osborn et al (2011) used isotopes of water, carbon, boron, and radium to test for hydraulic fracturing contamination of shallow aquifers overlying the Marcellus and Utica shale formations in Pennsylvania and New York, respectively, and found significant changes in CH 4 concentrations in drinking-water wells near locations where gas wells have been drilled. Limited research has also suggested that CH 4 -derived carbon is assimilated into stream food webs (Kohzu et al 2004;Trimmer et al 2010). Many gas-bearing geological formations also contain elevated levels of naturally occurring radioactive materials, such as radon ( 222 Rn) and radium ( 226 Ra, 228 Ra), that can be used as hydrological tracers (Genereux and Hemond 1990).…”
Section: Release Of Wastewatersmentioning
confidence: 99%